Magic and Witchcraft - Anonymous (Auckland : The Floating Press, 2013)
Dip into the mysterious world of sorcery with this comprehensive take on the topic. Published anonymously due to the incendiary nature of the subject matter, Magic and Witchcraft offers a historical overview of magic throughout the ages, all rendered in the deliciously ornate prose of the nineteenth century. Reading this volume is like poring over one of the musty old textbooks that Harry Potter and his fellow students would have been issued at Hogwarts School of Witchcraft and Wizardry.
Title; Contents; Preface; Magic and Witchcraft; Endnotes
Description based upon print version of record.
Keywords: Amulets -- History; Magic -- History; Witchcraft -- History; Magic -- History; Witchcraft -- History; BODY, MIND & SPIRIT / Parapsychology / General; Electronic books